Should I stay or should I go? Hormonal and demographic correlates of natal dispersal in a population of wild vervet monkeys - Van Blerk, Arend R (Department of Biological Sciences, 2022)
Natal dispersal is an important maturational milestone in the life of many primates and is associated with changes in the physical and social environment. To integrate into an unrelated group, an individual must abandon its known environment and face various challenges which can often be costly. Male dispersal is most common among Old World monkeys, but is poorly studied due to the difficulty of following dispersing individuals. Even fewer studies have attempted to explore the hormonal correlates of dispersal owing to the difficulties of obtaining sufficient faecal samples of the same individuals before, during and after a successful dispersal. In this study, I aimed to better understand the hormonal correlates (i.e. testosterone and cortisol) of dispersal in free ranging, habituated male vervets leaving their natal groups (natal dispersal). I collected faecal samples from 10 males and assessed the effects of age, rank, natal group size, adult sex ratio and number of same sex peers, to investigate potential influences on the triggers for natal male dispersal. My results show that standardised rank, but not testosterone levels, was significantly lower in the three months following a successful primary dispersal than before the animals left their natal group. Natal males from larger groups had significantly higher testosterone levels than those from smaller groups and dispersed significantly later than males from smaller groups. Cortisol levels were rarely above the minimum detection level, suggesting dispersal in vervets is not a stressful behaviour, possibly because of high levels of familiarity with individuals in troops into which males had immigrated. Limitations included the difficulty of following known individuals into habituated study troops, which resulted in a relatively small sample size of successfully dispersing males. Furthermore, a lack of adequate faecal samples at key points in the life history of individuals reduced resolution on pre- and post- dispersal hormonal correlates. Further studies will require a larger proportion of the study population to be habituated and regularly followed to allow for a more rigorous assessment of dispersal success and hormonal correlates. This study advances the limited knowledge we have on the potential drivers of male dispersal in vervets and primates more generally.